The Role of Social Media for PAI Teachers in The Student Learning Process at School: an Introduction to Education - Nurhuda, Abid; Ansori, Inamul Hasan; Aziz, Thariq (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Education aims to form a generation of faith and piety as mandated by the law. And realizing this goal is not easy so it requires a process and cooperation from various parties, including PAI teachers who have their homework related to moral degradation that is increasingly becoming. Especially in this era where technological sophistication has advanced so rapidly that social media has emerged. So it takes a more interesting packaging of material from PAI teachers to students in the learning process to hit the heart so that the hope can be applied in everyday life. So the purpose of this study is to describe the role of social media for PAI teachers in the student learning process at school. The method used is a literature study with a qualitative descriptive approach, data collected from various relevant sources, and then concluded. The results showed that social media became a separate innovation for PAI teachers during the learning process with students, especially in the current era, and it acts as a means of learning from several sources, as a means of administrative documentation and integration, then as a means of planning both strategically and management and finally as a means of control that includes evaluation and measurement. And with all of that, learners will easily absorb information, develop their potential, and be able to learn.